Simultaneous hydrolysis and fermentation of defatted rice bran and defatted soybean meal for nisin production with engineered Lactococcus lactis - Jiaheng Liu; Xiangyu He; Yuhui Du; Itsanun Wiwatanaratanabutr; Guangrong Zhao; Hongji Zhu; Qinggele Caiyin; Jianjun Qiao (My University, 2020)
This work aimed to study the potential of defatted rice bran (DRB) and defatted soybean meal (DSM) as carbon and nitrogen sources for Lactococcus lactis growth and nisin production. First, a maximum nisin yield of 3630 IU/mL was achieved using 40% DRB hydrolysates and 30% DSM hydrolysates, which was 1.13 times greater than that found in commercial media. Second, to simplify the operation and shorten the length of the entire process, the processes of combined hydrolysis of DRB-DSM followed by fermentation, and simultaneous hydrolysis and fermentation of DRB-DSM were developed. Neutral proteinase enhanced the saccharification of DRB by cellulase and α-amylase. Furthermore, the strategy of NADH oxidase expression and hemin addition was innovatively proposed to overcome the oxygen stress in a simultaneous hydrolysis and fermentation process, which could alleviate the lag period following inoculation of L. lactis and result in a 77.3% increase in nisin titer.
Keywords: Enzyme Production and Characterization